Analysis of Internal Factors That Influence The Interest of Students In Choosing The Digital Business Study Program of Bengkalis State Polytechnic - Bustami, Bustami; Custer, Jhonny; Pramadani, Kendra (Politeknik Negeri Bengkalis, 2024)
This study examines the internal factors influencing students' interest in choosing the Digital Business studyprogram at Politeknik Negeri Bengkalis. The research aims to identify which internal factors significantly impactstudents' decisions, determine the most dominant factors, and assess the factors with minimal influence. The studyemployed a survey method using questionnaires to collect data from students enrolled in the Digital Business program.Correlation and regression analyses, supported by statistical software, were used to analyze the data. The results revealthat Preference and Learning Method are the most influential internal factors, exerting the strongest impact on students'decision-making. Interest also plays a role, though less significant. Other factors, such as Attention, Willingness,Talent, Health, and Motivation, show minimal or no significant influence, with Attention and Willingness havingnegative coefficients. The regression model's confirms that the independent variables collectively influence students'interest, and the model indicates that 36.8% of the variance in interest is explained by the internal factors. Based onthe findings, it is recommended that the Digital Business program align its curriculum and teaching methods withstudents' preferences and create a student-centered learning environment to better attract and retain students.